Cerebral blood flow alterations associated with high volume caudal block in infants. (December 2020) - Castillo, Paul; Lundblad, Marit; Forestier, Jakob; Eksborg, Staffan; Lönnqvist, Per-Arne
Abstract: Background: High-volume (1.5 ml kg −1 ) caudal block in infants results in major reductions of cerebral blood flow velocity (CBFV) and cerebral oxygenation, caused by rostral CSF movement which increases intracranial pressure. The primary aim of this study was to determine the relationship between injected volume and CBFV changes. We hypothesised that this volume–blood flow relationship would have a similar albeit inverted shape to the well-known intracranial pressure volume–pressure curve. Methods: Fifteen subjects, age 0–6 months, mean (range) weight 4.9 (2.1–6.4) kg, were studied. A 1.5 ml kg −1 caudal injection of 0.2% ropivacaine was administered in three phases separated by two pauses. Subjects were randomised into five groups, in whom the pauses were implemented at different pre-set proportions of the total injected volume. Middle cerebral artery Doppler ultrasonography was used for CBFV measurements (Vmax, peak CBF velocity; Vmin, lowest CBF velocity; velocity time index). Mean flow velocity, pulsatility index, and resistivity index were calculated, and haemodynamic parameters were recorded. Results: CBFV parameters decreased in all patients. The most affected parameter, Vmin, was reduced by ∼50% (range 15–68%) compared with baseline. There was a nonlinear relationship between the volume of the first phase injection and the CBFV measurement during the first pause. Across all time points, there was a linear relationship between volume administered and CBFV. Systemic haemodynamic parameters remained stable throughout the study. Conclusions: Injection pauses appear to attenuate adverse CBFV increases during administration of a high-volume caudal block.